HMGB1 binds to the rs7903146 locus in TCF7L2 in human pancreatic islets. (15th July 2016) - Zhou, Yuedan; Oskolkov, Nikolay; Shcherbina, Liliya; Ratti, Joyce; Kock, Kian-Hong; Su, Jing; Martin, Brian; Oskolkova, Malin Zackrisson; Göransson, Olga; Bacon, Julie; Li, Weimin; Bucciarelli, Saskia; et al.
Abstract: The intronic SNP rs7903146 in the T-cell factor 7-like 2 gene ( TCF7L2 ) is the common genetic variant most highly associated with Type 2 diabetes known to date. The risk T-allele is located in an open chromatin region specific to human pancreatic islets of Langerhans, thereby accessible for binding of regulatory proteins. The risk T-allele locus exhibits stronger enhancer activity compared to the non-risk C-allele. The aim of this study was to identify transcriptional regulators that bind the open chromatin region in the rs7903146 locus and thereby potentially regulate TCF7L2 expression and activity. Using affinity chromatography followed by Edman sequencing, we identified one candidate regulatory protein, i . e . high-mobility group protein B1 (HMGB1). The binding of HMGB1 to the rs7903146 locus was confirmed in pancreatic islets from human deceased donors, in HCT116 and in HEK293 cell lines using: (i) protein purification on affinity columns followed by Western blot, (ii) chromatin immunoprecipitation followed by qPCR and (iii) electrophoretic mobility shift assay. The results also suggested that HMGB1 might have higher binding affinity to the C-allele of rs7903146 compared to the T-allele, which was supported in vitro using Dynamic Light Scattering, possibly in a tissue-specific manner. The functional consequence of HMGB1 depletion in HCT116 and INS1 cells was reduced insulin and TCF7L2 mRNA expression, TCF7L2 transcriptional activity and glucose stimulated insulin secretion. These findings suggest that the rs7903146 locus might exert its enhancer function by interacting with HMGB1 in an allele dependent manner. Highlights: High-mobility group protein B1 (HMGB1) binds the rs7903146 locus in HCT116 cells. HMGB1 binding was confirmed in human pancreatic islets using 2 different methods. HMGB1 possibly binds the C-allele with higher affinity compared to the T-allele. HMGB1 depletion reduces TCF7L2 mRNA and activity levels. HMGB1 depletion reduces insulin expression and glucose stimulated insulin secretion.